MODELOS GENÉTICOS E AMBIENTAIS NA EXPRESSÃO FENOTÍPICA DE LINHAGENS DE AVEIA BRANCA PARA AS CONDIÇÕES REGIONAIS - Costa, Juliane S. P.; Mantai, Rubia; Battisti, Gabriel K.; Fontaniva, Cristiano; Krüger, Cleusa A. M. B.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo